2012
DOI: 10.1128/jvi.01273-12
|View full text |Cite
|
Sign up to set email alerts
|

Adenovirus Regulates Sumoylation of Mre11-Rad50-Nbs1 Components through a Paralog-Specific Mechanism

Abstract: The Mre11-Rad50-Nbs1 (MRN) complex plays a key role in the DNA damage response, presenting challenges for DNA viruses and retroviruses. To inactivate this complex, adenovirus (Ad) makes use of the E1B-55K and E4-open reading frame 6 (ORF6) proteins for ubiquitin (Ub)-mediated, proteasome-dependent degradation of MRN and the E4-ORF3 protein for relocalization and sequestration of MRN within infected-cell nuclei. Here, we report that Mre11 is modified by the Ub-related modifier SUMO-2 and Nbs1 is modifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
83
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 34 publications
(90 citation statements)
references
References 58 publications
7
83
0
Order By: Relevance
“…In addition to sumoylation, E4-ORF3 decreased TIF-1γ and TFII-I, but not Nbs1, expression levels (Fig. 1B), consistent with previous reports (8,12). Additionally, we confirmed that E4-ORF3 mediates proteasomal degradation of TIF-1γ in HeLa and A549 cells using the proteasome inhibitor MG132 (Fig.…”
Section: Resultssupporting
confidence: 80%
See 4 more Smart Citations
“…In addition to sumoylation, E4-ORF3 decreased TIF-1γ and TFII-I, but not Nbs1, expression levels (Fig. 1B), consistent with previous reports (8,12). Additionally, we confirmed that E4-ORF3 mediates proteasomal degradation of TIF-1γ in HeLa and A549 cells using the proteasome inhibitor MG132 (Fig.…”
Section: Resultssupporting
confidence: 80%
“…2A), demonstrating that TIF-1γ sumoylation was enhanced by E4-ORF3 in the absence of any cellular SUMO E3 ligase. We also tested the E4-ORF3 L103A mutant, which is defective in formation of nuclear tracks and subsequent E4-ORF3 functions, including the sumoylation of target proteins (7,8). Interestingly, TIF-1γ sumoylation remained unchanged by addition of E4-ORF3 L103A in the same range of concentrations as wild-type, suggesting that E4-ORF3 self-assembly is required for this activity.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations